1997
DOI: 10.1128/jvi.71.3.1992-2003.1997
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA is a trigger for apoptosis in vaccinia virus-infected cells

Abstract: The vaccinia virus E3L gene codes for double-stranded RNA (dsRNA) binding proteins which can prevent activation of the dsRNA-dependent, interferon-induced protein kinase PKR. Activated PKR has been shown to induce apoptosis in HeLa cells. HeLa cells infected with vaccinia virus with the E3L gene deleted have also been shown to undergo apoptosis, whereas HeLa cells infected with wild-type vaccinia virus do not. In this report, using virus recombinants expressing mutant E3L products or alternative dsRNA binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(58 citation statements)
references
References 86 publications
2
55
0
1
Order By: Relevance
“…Importantly, PKR-overexpressing cells were also 3-fold more sensitive to apoptosis induced by influenza virus and parainfluenza virus, compared with control cells, while cells expressing PKRΔ6 were again resistant (data not shown). Our conclusions confirm a number of studies that have implicated a role for PKR in mediating programmed cell death in response to dsRNA and selected viral infections (Takizawa et al, 1996;Der et al, 1997;Kibler et al, 1997;Lee et al, 1997;King and Goodbourn, 1998;Srivastava et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, PKR-overexpressing cells were also 3-fold more sensitive to apoptosis induced by influenza virus and parainfluenza virus, compared with control cells, while cells expressing PKRΔ6 were again resistant (data not shown). Our conclusions confirm a number of studies that have implicated a role for PKR in mediating programmed cell death in response to dsRNA and selected viral infections (Takizawa et al, 1996;Der et al, 1997;Kibler et al, 1997;Lee et al, 1997;King and Goodbourn, 1998;Srivastava et al, 1998).…”
Section: Discussionsupporting
confidence: 90%
“…Vaccinia virus, for example, has been reported to encode two products that impede PKR activity. One protein, referred to as E3L, itself contains a DRBD and is primarily detected in the nucleus where it competes for dsRNA activators and may even bind to and inhibit the kinase through dsRNA bridging (53,54). A second vaccinia protein, referred to as K3L, shares homology to the known PKR substrate eIF2␣ and is thought to function by competitively sequestering the kinase (55)(56)(57).…”
Section: Protein Kinase Dsrna Dependent (Pkr)mentioning
confidence: 99%
“…Since RV replication requires the formation of replication complexes, it is likely that viral components such as dsRNA (84,91) and ns proteins (77) found within these structures play a role in the apoptotic process. Recent studies of vaccinia virus infection showed that dsRNA caused apoptosis via the activation of dsRNA-dependent protein kinase, a key player in interferon-mediated host defense against viral infection (5,39,72). While this has not been shown for RV, it is possible that the RV RI and RF RNAs may elicit similar responses; interestingly, alpha interferon is present in 90% of RV-infected fetuses and is readily detectable in the sera of fetuses at midgestation (21 to 29 weeks) (79).…”
Section: Apoptosismentioning
confidence: 99%